Simple Simulation of Perturb and Observe MPPT Algorithm on Synchronous Buck Converter - Abuzairi, Tomy; Rachmad, Ralfi Wibowo (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
The efficiency of the PV system can be improved by operating the solar panel on its Maximum Power Point (MPP). However, ariations in irradiance and temperature will lead to the shifting of solar panel MPP. To continuously operate the solar panel near its MPP, a tracking algorithm is needed. In this research, a model consisting of a synchronous buck converter and a Maximum Power Point Tracking (MPPT) algorithm will be designed as aMATLAB/Simulink model. Perturb and Observe technique will be used to implement the algorithm into the synchronous buck converter, which will control a 10 W solar panel load so it will operate near its MPP. Results show that the PV system model can track the Solar Panel MPP in various simulated irradiance.